TWO LINK ROBOT CONTROLLERS BASED ON FUZZY TYPE-2 AND HIGHER ORDER SLIDING MODE (International Journal of Engineering and Computer Science, 2013)
In this paper, the multi-variable control of a two-link robot is considered. Industrial robots, such as robot of two degrees, are the high acceptance in industry and academic environments. They are also a classic problem in robotics for testing and evaluating the new controllers. In this research, two controllers based on fuzzy type 2 and higher order silding mode are employed for this case. The implementation of these controllers on robot models shows a proper tracking for each link.